2016
DOI: 10.1186/s12887-016-0687-6
|View full text |Cite
|
Sign up to set email alerts
|

Test characteristics of common appendicitis scores with and without laboratory investigations: a prospective observational study

Abstract: BackgroundDespite the poor independent test characteristics of the white blood cell count (WBC) and neutrophil count (NC) in identifying appendicitis, common clinical decision supports including the Pediatric Appendicitis Score (PAS) and Alvarado Score (AS), require the WBC and NC values. Moreover, blood tests cause discomfort/pain to children and require time for processing results. Scores based on clinical information alone may be of benefit in the pediatric population. The objective of our study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 27 publications
0
32
2
1
Order By: Relevance
“…PPV of MAS in our study was 87.7% which is significantly higher 36.0% in Khanafer et al study 6 . NPV was 51.2% in our report which was significantly lower than 83.6% in Khanafer et al study 6 .…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…PPV of MAS in our study was 87.7% which is significantly higher 36.0% in Khanafer et al study 6 . NPV was 51.2% in our report which was significantly lower than 83.6% in Khanafer et al study 6 .…”
Section: Discussioncontrasting
confidence: 60%
“…In the study by Khanafer et al, sensitivity of MAS was 83.3% 6 . In the study by Macklin et al, sensitivity of modified Alvarado score ≥7 was 76.3 7 .…”
Section: Discussionmentioning
confidence: 94%
“…The weighted prevalence of AA was significantly (p < 0.001) higher in studies that used either “abdominal pain suspected of AA” or “right lower quadrant (RLQ) pain” as their inclusion criteria (19 studies, n = 7,510, AA prevalence = 42.8%, 95% CI = 41.7–43.9) compared to those that used “abdominal pain” or undifferentiated abdominal pain (two studies, n = 1,095, AA prevalence = 13.4%, 95% CI = 11.5–15.6).…”
Section: Resultsmentioning
confidence: 98%
“…Articles that only provided the final score with limited or no data on the variables were excluded . Twenty‐one studies were included in our review. The study selection process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…History and physical examination are still in the first line, but laboratory tests and imaging modalities are of great importance (5), because especially younger children have limitations in expressing themselves. Complete blood count (CBC) is in the first line of laboratory evaluation to diagnose appendicitis (6,7). White blood cell count (WBC) is studied well in the literature, but recently, there are several CBC parameters such as red blood cell distribution width (RDW), mean platelet volume (MPV), and platelet distribution width (PDW) associated with the diagnosis of appendicitis (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%